The TEAM Sports project - Campo, Mickaël (Réflexions Sport, 2024)
Funded by the France 2030 initiative as part of the “High-Performance Sport” Priority Research Program, the TEAM Sports project is a unique collaboration between five French sports federations (rugby, handball, football, volleyball, and basketball) and five internationally renowned research laboratories. Focused on studying collective dynamics and group emotions in high-performance contexts, this project has introduced significant innovations in performance optimization and scientific support strategies. Sixteen studies have provided insights into what leads an athlete to focus on individual interests (“I”) or to embrace a collective approach (“WE”), while also revealing the effects of collective identity on various performance factors. Knowledge, technological advancements, training methodologies, and educational programs: the project has delivered numerous resources for elite coaches and, more broadly, for federations in the area of mental conditioning specific to team sports. Beyond its major scientific and technological contributions, TEAM Sports has marked a historic opportunity to bring collective sports federations closer together, generating societal impacts that will extend well beyond the 2024 Paris Olympic Games.